CANNABIDIOL AS A FORM OF TREATMENT IN PATIENTS WITH POST-TRAUMATIC STRESS DISORDER OF VICTIMS OF VIOLENCE – COMPREHENSIVE REVIEW - Braga, Cristina; Ocon, Carlos Alberto; Constantino, Viviane Macedo; Fernandes, Antônio de Olival; Filoni, Eduardo; Filho, Alfredo Ribeiro; Aragão , Neylor Rodrigo Oliveira; Almeida , Jacqueline Cunha Cabral Azevedo; Santos, Gleyce Kelly de Brito Brasileiro; Moraes, Suzyanne Araújo; Douradinho, Christian; Lima, Lidiane Souza; et al. (Seven Editora, 2024)
Introduction. Violence as a social and public health problem, with a particular focus on its consequences, such as Post-Traumatic Stress Disorder (PTSD). According to the World Health Organization, violence encompasses the intentional use of physical force or power, threatening or harming individuals, groups, or communities. Objective: To describe the effects of Cannabidiol in patients with Post-traumatic Stress due to physical and psychological violence. Methodology: This is an integrative observational and retrospective systematic review, with the following exclusion criteria: non-empirical articles, non-indexed publications, a total of 545 articles related to post-traumatic stress and cannabidiol were found and only 13 articles were selected to present the results of this study. Results and discussion: The endogenous endocannabinoid system plays a significant role in the processing and extinction of fear memory. Cannabidiol (CBD), a non-psychoactive component of Cannabis sativa, has shown potential in the treatment of anxiety disorders, including PTSD. CBD interacts with the endocannabinoid system indirectly by increasing the availability of endocannabinoids like anandamide, which acts on CB1 receptors in the brain. This activation of the endocannabinoid system can help reduce the behavioral response to aversive memories and improve fear extinction. Final Thoughts: While early research on the effects of CBD on PTSD is promising, more studies are needed to determine its efficacy and safety, particularly in victims of violence. The sources also emphasize the need for greater awareness and accessibility to cannabinoid-based treatments for those who can benefit from them. DOI:https://doi.org/10.56238/sevened2024.031-038